Clinical Characteristics and Resistance Patterns of Pseudomonas aeruginosa Isolated From Combat Casualties. Issue 3 (1st July 2021) - Ford, Mary B; Mende, Katrin; Kaiser, Susan J; Beckius, Miriam L; Lu, Dan; Stam, Jason; Li, Ping; Stewart, Laveta; Tribble, David R; Blyth, Dana M
ABSTRACT: Introduction: Multidrug-resistant (MDR) Gram-negative infections complicate care of combat casualties. We describe the clinical characteristics, resistance patterns, and outcomes of Pseudomonas aeruginosa infections in combat casualties. Methods: Combat casualties included in the Trauma Infectious Disease Outcomes Study with infections with and without P. aeruginosa isolation during initial hospitalization were compared. Pseudomonas aeruginosa from initial wound, blood, and serial isolates (≥7 days from previous isolate) collected from June 2009 through February 2014 was subjected to antimicrobial susceptibility testing, pulsed-field gel electrophoresis, and whole genome sequencing for assessing clonality. Multidrug resistance was determined using the CDC National Healthcare Safety Network definition. Results: Of 829 combat casualties with infections diagnosed during initial hospitalization, 143 (17%) had P. aeruginosa isolated. Those with P. aeruginosa were more severely injured (median Injury Severity Score 33 [interquartile range (IQR) 27-45] vs 30 [IQR 18.5-42]; P < .001), had longer hospitalizations (median 58.5 [IQR 43-95] vs 38 [IQR 26-56] days; P < .001), and higher mortality (6.9% vs 1.5%; P < .001) than those with other organisms. Thirty-nine patients had serial P. aeruginosa isolation (median 2 subsequent isolates; IQR: 1-5), with decreasing antimicrobial susceptibility. Ten percent of P. aeruginosa isolates were MDR, associated with prior exposure to antipseudomonal antibiotics ( P = .002), with amikacin and colistin remaining the most effective antimicrobials. Novel antimicrobials targeting MDR Gram-negative organisms were also examined, and 100% of the MDR P. aeruginosa isolates were resistant to imipenem/relabactam, while ceftazidime/avibactam and ceftolozane/tazobactam were active against 35% and 56% of the isolates, respectively. We identified two previously unrecognized P. aeruginosa outbreaks involving 13 patients. Conclusions: Pseudomonas aeruginosa continues to be a major cause of morbidity, affecting severely injured combat casualties, with emergent antimicrobial resistance upon serial isolation. Among MDR P. aeruginosa, active antimicrobials remain the oldest and most toxic. Despite ongoing efforts, outbreaks are still noted, reinforcing the crucial role of antimicrobial stewardship and infection control.